The World Turned : Essays on Gay History, Politics, and Culture - D'Emilio, John (Book collections on Project MUSE., 2002)
Distinguished historian and leading gay-rights activist D'Emilio show how gay issues moved from the margins to the center of national consciousness during the critical decade of the 1990s.